LANGUAGE IN THE POEM – HEIDEGGER’S TOPOLOGICAL INTERPRETATION ON TRAKL’S POETRY - Radovanović, Saša Ž (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2016)
The author opens the problem of Heidegger’s topological interpretation of poetry of Georg Trakl. The text sets the first problem the nature of topological interpretation of art, bearing in mind the interpretation which has been conducted in The Origin of Artwork. Then the author shows that Heidegger’s thoughtful reflection on the role of art in the era the techniques following Trakl poetic reflection on the role of the poet in the said epoch. Such dialogue singing and thinking is then viewed through Heidegger’s views on the thinking as to the original ethics set forth in the Letter of Humanism.